Use of spatiotemporal image correlation at 11–14 weeks' gestation. (December 2013) - Votino, C.; Cos, T.; Abu‐Rustum, R.; Dahman Saidi, S.; Gallo, V.; Dobrescu, O.; Dessy, H.; Jani, J.
ABSTRACT Objective To assess prospectively the use of four‐dimensional (4D) spatiotemporal image correlation (STIC) in the evaluation of the fetal heart at 11–14 weeks' gestation. Methods The study involved offline analysis of 4D‐STIC volumes of the fetal heart acquired at 11–14 weeks' gestation in a population at high risk for congenital heart disease (CHD). Regression analysis was used to investigate the effect of gestational age, maternal body mass index, quality of the 4D‐STIC volume, use of a transvaginal vs transabdominal probe and use of color Doppler ultrasonography on the ability to visualize separately different heart structures. The accuracy in diagnosing CHD based on early fetal echocardiography (EFE) using 4D‐STIC vs conventional two‐dimensional (2D) ultrasound was also evaluated. Results One hundred and thirty‐nine fetuses with a total of 243 STIC volumes were included in this study. Regression analysis showed that the ability to visualize different heart structures was correlated with the quality of the acquired 4D‐STIC volumes. Independently, the use of a transvaginal approach improved visualization of the four‐chamber view, and the use of Doppler improved visualization of the outflow tracts, aortic arch and interventricular septum. Follow‐up was available in 121 of the 139 fetuses, of which 27 had a confirmed CHD. A diagnosis based on EFE using 4D‐STIC was possible in 130 (93.5%) of the 139 fetuses. Accuracy in diagnosing CHD using 4D‐STIC was 88.7%, and the results of 45% of the cases were fully concordant with those of 2D ultrasound or the final follow‐up diagnosis. EFE using 2D ultrasound was possible in all fetuses, and accuracy in diagnosing CHD was 94.2%. Five of the seven false‐positive or false‐negative cases were minor CHD. Conclusions In fetuses at 11–14 weeks' gestation, the heart can be evaluated offline using 4D‐STIC in a large number of cases, and this evaluation is more successful the higher the quality of the acquired volume. 2D ultrasound remains superior to 4D‐STIC at 11–14 weeks, unless volumes of good to high quality can be obtained. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.